Ruxolitinib is effective in the treatment of a patient with refractory T‐ALL. Issue 1 (4th December 2020) - Jaramillo, Sonia; Hennemann, Hannah; Horak, Peter; Teleanu, Veronica; Heilig, Christoph E.; Hutter, Barbara; Stenzinger, Albrecht; Glimm, Hanno; Goeppert, Benjamin; Müller‐Tidow, Carsten; Fröhling, Stefan; Schönland, Stefan; et al.
Abstract: T‐cell acute lymphoblastic leukemia (T‐ALL) is a rare, aggressive T‐cell malignancy. Chemotherapy alone cures only 25‐45% of the cases, thus, novel treatment agents and strategies are urgently needed. We assessed the efficacy of ruxolitinib in a patient with a cutaneous relapse after allogeneic blood cell transplantation of a refractory T‐ALL with a Janus kinase 3 ( JAK3 ) mutation. In this case report, we were able to show the potential benefit of the JAK inhibitor ruxolitinib in JAK3 ‐mutated refractory T‐ALL and emphasize the importance of integrating molecular markers in current treatment decision making for patients with T‐ALL.